2022
DOI: 10.1038/s41559-022-01894-w
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic divergence during early stages of speciation in an African crater lake cichlid fish

Abstract: Epigenetic variation can alter transcription and promote phenotypic divergence between populations facing different environmental challenges. Here, we assess the epigenetic basis of diversification during the early stages of speciation. Specifically, we focus on the extent and functional relevance of DNA methylome divergence in the very young radiation of Astatotilapia calliptera in crater Lake Masoko, southern Tanzania. Our study focuses on two lake ecomorphs that diverged approximately 1,000 years ago and a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…GO terms enriched in benthic ecomorphs are related to blood cell development, vascular morphogenesis and metabolic oxidation-reduction processes. This may indicate local adaptation to increased habitat depth ( Jacobs and Elmer 2021 ; Vernaz et al 2022 ) and, more specifically, to the relatively low oxygen conditions of the deep-water benthic environment in Lake Masoko, compared with shallow-water habitat ( fig. 1 B and supplementary table S5, Supplementary Material online).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GO terms enriched in benthic ecomorphs are related to blood cell development, vascular morphogenesis and metabolic oxidation-reduction processes. This may indicate local adaptation to increased habitat depth ( Jacobs and Elmer 2021 ; Vernaz et al 2022 ) and, more specifically, to the relatively low oxygen conditions of the deep-water benthic environment in Lake Masoko, compared with shallow-water habitat ( fig. 1 B and supplementary table S5, Supplementary Material online).…”
Section: Resultsmentioning
confidence: 99%
“…There are many alternative molecular mechanisms through which rapid transcriptional and phenotypic diversity can be generated that were not explored here. Specifically, microRNAs, transposable elements, and epigenetic markers are recently shown to facilitate adaptive phenotypic shifts in cichlids ( Xiong et al 2019 ; Carleton et al 2020 ; Vernaz et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic modifications may take a variety of forms, these include DNA methylation (DNAm), histone modifications and noncoding RNA activity, all of which can regulate gene expression without requiring changes in the DNA sequence (Moore et al, 2013). Differential patterns of epigenetic modification have been associated with early stages of speciation (Vernaz et al, 2021(Vernaz et al, , 2022Vogt, 2017) DNAm involves the transfer of a methyl group to a cytosine base (Moore et al, 2013) and can occur throughout the genome but mostly occurs on CpG dinucleotide sites (Moore et al, 2013).…”
mentioning
confidence: 99%
“…Previous studies have shown that methylation is affected by temperature (Ryu et al 2018;Venney et al 2022;Metzger & Schulte 2017;McCaw et al 2020;Anastasiadi et al 2017), salinity (Heckwolf et al 2020;Artemov et al 2017), rearing environment (Leitwein et al 2021;Le Luyer et al 2017;Wellband et al 2021;Gavery et al 2018), and other factors in various systems. Differences in habitat use can influence DNA methylation, as observed between capelin (Mallotus villosus) utilizing beach-and demersal-spawning life history tactics (Venney et al 2023), among sympatric Arctic charr morphs occupying different habitats and dietary niches (Matlosz et al 2022), between phenotypically divergent cichlid species (Vernaz et al 2022), and in freshwater snails (Potamopyrgus antipodarum) which exhibit differences in shell shape associated with water current speed (Thorson et al 2017).…”
Section: Epigenetic Divergence Between Whitefish Species Pairsmentioning
confidence: 99%